THE EFFECT OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) COMBINED WITH BOBATH ON POST STROKE SPASTICITY. A RANDOMIZEDCONTROLLED STUDY - Tabish Hussain; Tumenjavkhlan Sosorburam; Hassan Mohammad (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: Spasticity is a vital component and one of the diagnostic features of upper motor neuron lesions and syndromes accompanied with it. This abnormal excessive muscle tone can lead to secondary complications such as pain, joint contracture, pressure ulcers and gait disturbance. Studies have reported that electrical stimulation of acupoint is effective in treatment of stroke patients with spastic hypertonia. The aim of this study was to evaluate the effectiveness of combined Bobath-TENS therapy in relation to simple Bobath among patients suffered from stroke and is in the rehabilitation phase of their disease presenting with spastic paralysis. Methods: A randomized controlled trial was conducted at the Rehabilitation department of Tongji medical hospital. A total of 30 stroke patients with ankle plantar flexor spasticity were recruited. The mean age of the patients was 55.2 years (range 37-70 years) and the mean duration of stroke was 4.73 months (range 3 to 8 months). The patients were randomly assigned to two groups; 15 patients each were assigned to each group. Patients in the control group received 15 minutes of inhibitory Bobath technique. Patients in the study group received a combination of 30 minutes of TENS on lower leg acupuncture points along with inhibitory Bobath techniques for 4 weeks, 5 days a week. Muscle tonus (MAS) score of the affected ankle, passive ankle joint dorsiflexion range of motion, dorsiflexion strength test, gait speed and the Brunnstrom stages of motor recovery were noted as the final outcome so as to compare the two groups. Results The combined therapy study group with TENS-Bobath showed extremely successful results in terms of selected parameters. All the parameters turned out to be statistically significant (P<0.05).Ankle passive dorsiflexion movement improved massively followed by 10 meters walk test in the combination therapy group. Although, Bobath only therapy control group was also statistically significant, but the level of significance was much marked in the combined study group. Conclusion: 20 sessions of TENS combined with Bobath decreased plantar flexor spasticity, improved dorsiflexors strength, and increased gait velocity significantly more than Bobath alone.